Effect of reactor operation modes on mitigating antibiotic resistance genes (ARGs) and methane production from hydrothermally-pretreated pig manure - Guo, Chunchun; Lin, Shupeng; Lyu, Tao; Ma, Yanfang; Dong, Renjie; Liu, Shan (Elsevier, 2024)
Numerous efforts have been made to enhance the performance of anaerobic digestion (AD) for accelerating renewable energy generation, however, it remains unclear whether the intensified measures could enhance the proliferation and transmissions of antibiotic resistance genes (ARGs) in the system. This study assessed the impact of an innovative pig manure AD process, which includes hydrothermal pretreatment (HTP) and a two-stage configuration with separated acidogenic and methanogenic phases, on biomethane (CH4) production and ARGs dynamics. Results showed that HTP significantly increase CH4 production from 0.65 to 0.75 L/L/d in conventional single-stage AD to 0.82 and 0.91 L/L/d in two-stage AD. This improvement correlated with a rise in the relative abundance of Methanosarcina, a key methanogenesis microorganism. In the two-stage AD, the methanogenic stage offered an ideal environment for methanogens growth, resulting in substantially faster and higher CH4 production by about 10% compared to single-stage AD. Overall, the combined use of HTP and the two-stage AD configuration enhanced CH4 production by 40% compared to traditional single-stage AD. The abundance and diversity of ARGs were significantly reduced in the acidogenic reactors after HTP. However, the ARGs levels increased by about two times in the following methanogenesis stage and reached similar or higher levels than in single stage AD. The erm(F), erm(G), ant(6)-Ia, tet(W), mef(A) and erm(B) were the six main ARGs with significant differences in relative abundances in various treatments. The two-stage AD mode could better remove sul2, but it also had a rebound which elevated the risk of ARGs to the environment and human health. Network analysis identified pH and TVFAs as critical factors driving microbial communities and ARG proliferation in the new AD process. With the results, this study offers valuable insights into the trade-offs between AD performance enhancement and ARG-related risks, pinpointing essential areas for future research and practical improvements.
Keywords: Antimicrobial resistance (AMR); Livestock manure; Metagenomics investigation; Sustainable biowaste treatment; Two-stage anaerobic digestion